Blood Pressure Modulation With Low-Intensity Focused Ultrasound Stimulation to the Vagus Nerve: A Pilot Animal Study - Ji, Ning; Lin, Wan-Hua; Chen, Fei; Xu, Lisheng; Huang, Jianping; Li, Guanglin (Frontiers in Neuroscience, 2020)
Objective: For hypertensive individuals, their blood pressure (BP) is often managed by taking medications. However, antihypertensive drugs might cause adverse effects such as congestive heart failure and are ineffective in significant numbers of hypertensive population. As alternative method for hypertension management, non-drug devices-based neuromodulation approaches such as functional electrical stimulation (FES) have been proposed. FES approach requires the implantation of a stimulator into body. One recently emerging technique, called low-intensity focused ultrasound stimulation (LIFUS), has been proposed to non-invasively modulate neural activities. In this pilot study, the feasibility of adopting LIFUS neuromodulation for BP regulation was investigated using animal models. Methods: A LIFUS system was developed for BP modulation in rabbits. For each rabbit, the LIFUS with different acoustic intensities was used to stimulate its exposed left vagus nerve, and the BP waveform was synchronously recorded in its right common carotid artery. The effects of the different LIFUS intensities on systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterial pressure (MAP), and heart rate (HR) were extensively examined from the BP recordings. Results: The results demonstrated that the proposed LIFUS method could successfully induce changes in SBP, DBP, MAP, and HR values. When increasing acoustic intensities, the values of SBP, DBP, and MAP would decrease more substantially. Conclusion: The findings of this study suggested that BP could be modulated through the LIFUS, which might provide a new way for non-invasive and non-drug management of hypertension.